Copper Contamination of Different Prawn Farms at Shatkhira District - Ali, ML; Sattar, MA; Baten, MA (Journal of Environmental Science and Natural Resources, 2012)
Copper (Cu) contamination of six prawn farms under three upazilas of Satkhira district were evaluated. Total 54 water, sediment and prawn samples were collected from six farms, 18 samples from each category were examined to observe the Cu contamination of water, sediment and prawn. Cu was determined by Atomic Absorption Spectrophotometer at the central laboratory of Bangladesh Agricultural University and toxicity laboratory of Bangladesh Fisheries Research Institute, Mymensingh. The levels of Cu in water sample, sediment sample and samples of prawn species were collected from different surface and ground sources. The concentration of Cu in sediment samples were ranged from 45.3895 to 127.8771 ?g-1 and the average mean concentration was 76.92101 ?g-1. The concentration of Cu in prawn was ranged from 16.1069 to 97.3841 ?g-1 and the average mean concentration was 51.2342 ?g-1. The copper concentration in water ranged from 0.0309 to 0.0702 ppm. Cu concentrations in those samples were higher in sediment than prawn, but very lower concentration was found in water sample. The Cu in sediment samples were present higher amount than allowable limit. So prawn was mostly affected by contaminated water and sediment. DOI: http://dx.doi.org/10.3329/jesnr.v4i2.10157 J. Environ. Sci. & Natural Resources, 4(2): 105-109, 2011